The Rise of Religious Radicalism Among Teenager - Shaffa Hiyatma; Siti Nurul Hidayati; Daffa Ramadhani Yanuar (PT Pro Panoramic Solution, 2025)
The rise of religious radicalism among teenagers has become a significant concern in recent years. Due to their vulnerability and susceptibility to influence, this age group is often targeted by radical groups. Factors like the search for identity, social isolation, and exposure to misinformation on social media contribute to their susceptibility. This research aims to examine the causes, impacts, and strategies for addressing religious radicalism among teenagers, utilizing qualitative methods such as interviews, surveys, and literature analysis. The research results show that factors such as a lack of comprehensive understanding of religion, the influence of the social environment, and access to radical information through social media contribute significantly to the spread of radicalism. To prevent the spread of radical ideas among teenagers, this research recommends several strategies, such as strengthening moderate religious education, character development programs, and increasing awareness of the dangers of radicalization through social campaigns. It's essential for parents, educators, and society to work together to foster values of tolerance and peace. This study emphasizes that prevention efforts should include inclusive education, digital literacy, and psychosocial support from families and communities. The findings aim to inform preventive policies that protect the younger generation from radical influences.